Data Protection of Big Data in Cloud Environment and Its Security Measures for Super Marketing: Understanding Cloud Computing Security Measures for Big Data Protection in Super Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cloud computing is an internet based computing platform which is shared information, hardware and software resources, is provided to computers and devices on-demand, like the power grid. It is a great idea to make many standard computers together to get a super computer where it can do a lot of things powerfully. It aims to construct a perfect system with powerful computing capability through a large number of relatively low-cost computing unit, and using the innovative business models like SaaS, PaaS, and IaaS to distribute the powerful computing capacity to end user’s hands. This paper provides a snapshot of cloud computing background, classifications, service model, existing security issues and typical security measures.